A seasonal pattern in the onset of polymyalgia rheumatica. Issue 7 (July 1990) - Cimmino, M A; Caporali, R; Montecucco, C M; Rovida, S; Baratelli, E; Broggini, M
Abstract : The seasonal distribution in the onset of polymyalgia rheumatica (PMR) was determined in 58 patients with the disease and compared with that in 44 patients affected by rheumatoid arthritis of elderly onset (EORA). Thirty six (62%) cases of PMR developed during May to August; by contrast, only 14 (31%) cases of EORA developed in the same months, this latter disease failing to show any seasonal clustering. The monthly distribution of PMR correlated with outside temperature and hours of sunshine. These data suggest that PMR might be triggered by such factors as actinic damage of superficial vessels or infective agents with a seasonal cycle. Finally, the summer clustering of PMR may be helpful in the differential diagnosis from EORA.